Factors leading to successful island rodent eradications following initial failure. Issue 6 (11th March 2021) - Samaniego, Araceli; Kappes, Peter; Broome, Keith; Cranwell, Steve; Griffiths, Richard; Harper, Grant; McClelland, Pete; Palmer, Russell; Rocamora, Gérard; Springer, Keith; Will, David; Siers, Shane
Abstract: Island rodent eradications are increasingly conducted to eliminate the negative impacts of invasive rodents. The success rate in the tropics has been lower than in temperate regions, triggering research and reviews. Environmental factors unique to the tropics (e.g., land crabs and year‐round rodent breeding) have been associated with eradication failure. Operational factors have also been important, but these have not been comprehensively assessed. The environmental and operational factors using global cases where rodent eradication initially failed and subsequent attempts occurred were compared. It was determined whether operational factors explained the initial failures, whether operational improvements explained subsequent successes, and whether re‐attempting eradication after failure was worthwhile. About 35 eradication attempts on 17 islands, each with 1–2 species from a total of 5 species ( Mus musculus and 4 Rattus spp.) were identified. On 14 islands (82%), eradication was achieved on the second (86%) or third attempt (14%). On the remaining 3 islands, eradication was not achieved. Evidence of operational faults for all failed attempts was found (e.g., poor planning, low quality bait, and gaps during bait application). In some cases, operational faults were unequivocally the cause of failure, but in others, it was impossible to discriminate from confounding, environmental factors. Nonetheless, failures appeared to be mainly the result of not exposing all rodents to a lethal dose of toxin, violating a crucial eradication principle. This can cause operational failure on any temperate or tropical island. However, there may be less tolerance for errors such as gaps in bait coverage on tropical islands, mainly due to bait consumption by land crabs. The findings on factors leading to eradication success (e.g., expert reviewed plans, realistic funding and permits, high standard baiting operations) reflect current best practice recommendations. Strict adherence to best practice is expected to increase overall rates of eradication success.